Pattern Formation Scenario through Turing Instability in Interacting Reaction-Diffusion Systems with Both Refuge and Nonlinear Harvesting - Guin, Lakshmi Narayan; Das, Esita; Sambath, Muniyagounder (Journal of Applied Nonlinear Dynamics, 2026)
Of concern in the present theoretical study is to carry out the complex dynamics of a reaction-diffusion predator-prey model incorporating constant proportion of prey refuge and nonlinear prey harvesting with zero-flux boundary conditions. By the method of Lyapunov function, the global stability of the feasible interior equilibrium point for nonspatial model was established. The conditions of diffusion-driven instability were obtained and the Turing space in the parameters space was given as well. Consequently, we present the evolutionary procedure that occupies organism distribution and their interaction of spatially distributed species with diffusion and locate that the model dynamics reveals a diffusion-controlled formation growth to hole patterns or labyrinthine patterns or hole-stripe patterns replication over the whole spatial domain. The analytical results are then authenticated with the help of numerical simulations. Our results points out that the diffusion has an immense impact on the prey refuge as well as prey harvesting and extend well the findings of spatiotemporal dynamics in the reaction-diffusion model.